Comprehensive of Price Level Changes In Evaluation & Accounting Purpose: Understanding the Importance of Profit and Accounting in Business (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A business comes into existence primarily to make profit.  In this attempt it provides goods andservices to the community.  It alsoprovides means of livelihood to some members of the community by creatingemployment opportunities. These are sound subsidiary or secondary motives. Theall-important motives of a running business however is to makeprofit."PROFIT TO A BUSINESS IS LIKE FOOD TO A HUMAN BODY : THE BODY MUSTGROW AND DEVELOP – WITH THE ASSISTANCE OF FOOD. TAKE AWAY THE SUPPLY OF FOOD AND THE BODY WASTES AWAY AND DIES."Every type of businessman to find out the amount of profit earned during acertain period (called Accounting Period) usually an year. In order to find outthe amount of profit or loss, he must have a complete and  systematic record of the business  transactions i.e. dealings in money ormonetary terms, entered into during the fiscal year.